Chemometric – assisted UV spectrophotometric method for determination of antihyperlipidemic agents in pharmaceutical formulation - Gandhi, Santosh V; Mutha, Amit S (Journal of Applied Pharmaceutical Research, 2017)
This presented work is based on application of two multivariate calibration methods for simultaneous UV-VIS spectrophotometric determination of active substances in combined pharmaceutical formulation composed of Atorvastatin calcium (ATV) and Ezetimibe (EZT). The methods used were Principal Component Regression (PCR) and Partial Least Square (PLS). The Spectra of ATV and EZT were recorded at concentrations within their linear range 5.0-30.0 μg/ml for both drugs. 28 set of mixtures were used for calibration and 08 set of mixtures were used for validation in the wavelength range of 230 to 260 nm with the wavelength intervals λ= 0.5 nm in methanol. The methods were validated as per International Conference on HarmonizationQ2 (R1) (ICH) guidelines. These methods were successfully applied for determination of drugs in pharmaceutical formulation (tablet) with no interference of the excipient as indicated by the recovery study results. The proposed methods are simple, rapid and can be easily used as an alternative analysis tool in the quality control as well as in process control of drugs and formulation.